Physiological and psychological recovery in two pure forests: interaction between perception methods and perception durations - Sun, Xiaogang; Li, Qinglan; Zhang, Xin; Sun, Miao; Yin, Jiahui; He, Jingyi; Zhong, Yige; Ning, Wei (Frontiers in Public Health, 2024)
The forest experience is good for people’s physical and mental health. However, few studies on the effects of pure forest based on the duration and way of experience on people’s physical and mental recovery. In this study, we took 180 first-year college students as research objects and conducted experiments in Pinus sylvestris and Betula platyphylla and the control group of grass plot. The changes of physiological and psychological indexes of the subjects were compared by two perception methods (onsite perception, video perception) and three perception duration (10 min, 20 min, 30 min). The results indicated that: (1) Differences between the two pure forests were mainly reflected in short-term recovery of diastolic blood pressure (DBP) and long-term recovery of total mood disorder (TMD). (2) Video perception was more conducive to short-term recovery of systolic blood pressure (SBP) and diastolic blood pressure (DBP). (3) Viewing the Pinus sylvestris for 20 min in different ways was the best way to relieve stress. It is suggested that, Pinus sylvestris can be used as the rehabilitation perception material, and reasonable path length or perception time can be selected for landscape construction in future. These results can provide scientific reference for landscape design based on forest health and environmental perception.